IMPLEMENTASI NAIVE BAYES CLASSIFIER DALAM MENENTUKAN KEAKTIFAN REMAJA - Surbakti, Miftah Hadi; Zufria, Ilka; Suhardi, Suhardi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: This research aims to implement the Naive Bayes Classifier method to determine the activity level of adolescents, a group that tends to be active in various activities. This method is chosen due to its ability to classify complex data. The data is obtained through surveys involving adolescents from different social environments, covering activities such as sports, academics, social engagements, and others. The implementation process includes data preprocessing, model training with training data, and model testing using test data. The results show that the Naive Bayes Classifier can accurately classify adolescents into active or inactive categories based on the given data. These findings can serve as a reference for educational institutions, youth organizations, and government bodies in developing programs to enhance adolescent activity levels and as a basis for further research in classifying adolescent data using more advanced methods. Keywords: Data Mining, Youth Activeness, Mosque Youth, Naïve Bayes Classifier,                  Medan City Abstrak: Penelitian ini bertujuan untuk mengimplementasikan metode Naive Bayes Classifier dalam menentukan keaktifan remaja, yang merupakan kelompok usia aktif dalam berbagai kegiatan. Metode ini dipilih karena kemampuannya dalam klasifikasi data kompleks. Data diperoleh melalui survei terhadap remaja di berbagai lingkungan sosial, mencakup kegiatan olahraga, akademik, sosial, dan lainnya. Proses implementasi meliputi preprocessing data, pelatihan model dengan data latih, dan pengujian model menggunakan data uji. Hasil penelitian menunjukkan bahwa Naive Bayes Classifier mampu secara akurat mengklasifikasikan keaktifan remaja menjadi kategori aktif atau tidak aktif berdasarkan data yang ada. Hasil ini dapat menjadi acuan bagi lembaga pendidikan, organisasi pemuda, dan pemerintah dalam menyusun program untuk meningkatkan keaktifan remaja serta menjadi dasar untuk penelitian lanjutan dalam pengklasifikasian data remaja menggunakan metode lebih canggih. Kata kunci: Data Mining, Keaktifan Remaja, Remaja Masjid, Naïve Bayes Classifier, Kota Medan